Foetal Alcohol Spectrum Disorder and its ethical impacts on society - Elaine Coates, David Junior Gilbert (BioScientist: The Salford Biomedicine Society Magazine, 2024)
<p class="OutlineElement Ltr SCXW42634548 BCX8" style="-webkit-user-drag: none; -webkit-tap-highlight-color: transparent; margin-bottom: 0px; user-select: text; clear: both; cursor: text; overflow: visible; position: relative; direction: ltr; color: rgb(0, 0, 0); font-family: "Segoe UI", "Segoe UI Web", Arial, Verdana, sans-serif; font-size: 12px;"> <p class="Paragraph SCXW42634548 BCX8" paraid="1032848975" paraeid="073f7104-3ebe-400f-ae04-d3143d0ed627220" style="-webkit-user-drag: none; -webkit-tap-highlight-color: transparent; margin-bottom: 10.6667px; user-select: text; overflow-wrap: break-word; vertical-align: baseline; font-kerning: none;">Foetal Alcohol Spectrum Disorder (FASD) is a range of neurological and physical conditions caused by prenatal exposure to alcohol. Alcohol can damage developing cells in various ways, and the impact will vary depending on the amount, duration and timing of the alcohol exposure. There is no safe limit, but women may be unaware of the risks or may drink before they realise they are pregnant. <p class="Paragraph SCXW42634548 BCX8" paraid="1032848975" paraeid="073f7104-3ebe-400f-ae04-d3143d0ed627220" style="-webkit-user-drag: none; -webkit-tap-highlight-color: transparent; margin-bottom: 10.6667px; user-select: text; overflow-wrap: break-word; vertical-align: baseline; font-kerning: none;">Dr David Junior Gilbert is part of the multi-disciplinary FASD research group at Salford University, which investigates various aspects of FASD. Dr Gilbert’s research is specifically focuses on the behavioural impacts. This article describes his current research into suggestibility and confabulation in adolescents with FASD, and how this affects their vulnerability, particularly in interactions with the criminal justice system. <p class="Paragraph SCXW42634548 BCX8" paraid="1032848975" paraeid="073f7104-3ebe-400f-ae04-d3143d0ed627220" style="-webkit-user-drag: none; -webkit-tap-highlight-color: transparent; margin-bottom: 10.6667px; user-select: text; overflow-wrap: break-word; font-kerning: none; font-size: 14px;">Greater awareness of FASD among social workers, medical professionals and within the justice system will help to facilitate earlier intervention and enable affected individuals more appropriately supported. It is estimated to affect 2-3% of children in the UK7, and these children are far more likely to encounter the criminal justice system (CJS) than children without FASD3. Elaine Coates spoke to Salford research fellow Dr David Junior Gilbert about the research being done at Salford on FASD. <p class="Paragraph SCXW42634548 BCX8" paraid="1032848975" paraeid="073f7104-3ebe-400f-ae04-d3143d0ed627220" style="-webkit-user-drag: none; -webkit-tap-highlight-color: transparent; margin-bottom: 10.6667px; user-select: text; overflow-wrap: break-word; font-kerning: none; font-size: 14px;">The Editorial Team would like to thank Dr David Junior Gilbert for his time and contributions to this article.
Keywords: brain abnormalities; prenatal alcohol exposure; pregnancy; infancy; criminal justice system; confabulation; FASD awareness